CLINICAL AND IMMUNOLOGICAL STATUS IN PATIENTS WITH LUNG ABSCESSES AND SEARCH FOR WAYS TO CORRECT THEM - Bobokulova, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. Most clinicians explain the increase in the number of patients with lung abscesses by environmental changes, a decrease in the standard of living, which leads to a violation of the antimicrobial resistance of the body and contributes to the development of destructive processes in the lungs. Material and methods. The work was carried out on the basis of the multidisciplinary clinic of the Tashkent Medical Academy. A total of 131 people were examined, including 94 patients with lung abscesses and 37 donors, who made up the control group of healthy individuals. Results. For the first time, a decrease in the number of lymphocytes carrying pan-T cell markers, but also the CD4 subpopulation, the ratio of CD4/CD8 cells and the number of cells expressing CD16 and CD71 receptors in the circulation of patients with acute lung abscesses was shown, which indicates a violation of cellular mechanisms of immunity. SZ and C5 in lung abscesses and growth of the baseline level of IL-6, without a significant increase in the amount of IL-8 in the blood serum. For the first time, an increase in the amount of IL-4 in lung abscesses at the systemic level was shown. Conclusion. The pathogenetic substantiation of the expediency of using the actoprotective drug bemityl in the complex postoperative treatment of lung abscesses contributes to the normalization of the composition of lymphocytes, the activity of the components of the classical complement activation pathway and the optimization of the excretion of circulating immune complexes.